Policing extremism on gaming-adjacent platforms: awful but lawful? - Allchorn, William; Orofino, Elisa (Frontiers in Psychology, 2025)
Since the inception of video games, extremist groups have been able to create, modify, and weaponise this medium for activism and propaganda. More recently, the emergence of gaming-adjacent platforms (most notably Discord, Twitch, and Steam) has provided a key organizational infrastructure for recruitment and community building. This development poses a significant challenge for policing communities worldwide, particularly have been grappling with, especially in regard to the potential for extremist content to given the potential for extremist content on these platforms to contribute to radicalization and political violence. This article explores how policing communities are responding to extremist activity on gaming-adjacent platforms, the strategies they employ, and the effect these approaches have on extremist activism both online and, more crucially, offline. Using semi-structured interviews with 13 leading P/CVE practitioners, academic and technology industry experts, and content moderation teams, the article finds that third-party policing communities are adopting increasingly sophisticated tactics to counter extremist content. However, these efforts are increasingly undermined by the networked and adaptive nature of extremism, as well as by insufficient enforcement mechanisms at the platform level. In the future, this research suggests that fostering greater transparency in terms of service enforcement from above, combined with efforts to counter toxic and extremist-“adjacent” cultures from below, may enhance resilience against the spread of extremism on gaming-adjacent platforms.